2004
DOI: 10.1093/intimm/dxh024
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical alteration of acute-phase protein levels in patients with chronic hepatitis C treated with IFN- 2b

Abstract: Previously we observed elevation of the serum concentration of two acute-phase protein (AFP) complement components (C9 and C1-inhibitor) in patients with chronic hepatitis C who responded (R) to IFN-alpha therapy, but not in non-responders (NR). In the present study we investigated the effect of high-dose IFN-alpha therapy on serum concentrations of two positive [orosomucoid (OROSO) and C-reactive protein (CRP)] and two negative [transferrin (TF) and fetuin/alpha2HS-glycoprotein (AHSG)] AFP in an outpatient se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
(13 reference statements)
4
13
0
1
Order By: Relevance
“…Previous studies have shown different patterns of CRP alteration according to the type of liver disease. Thus, it has been reported to be increased in alcoholic hepatitis [3], unchanged in non-alcoholic steatohepatitis [11], and decreased in chronic hepatitis C [12]. Most of our patients had liver disease secondary to hepatitis C virus infection, providing an explanation for the observed trend of decreased CRP concentrations.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have shown different patterns of CRP alteration according to the type of liver disease. Thus, it has been reported to be increased in alcoholic hepatitis [3], unchanged in non-alcoholic steatohepatitis [11], and decreased in chronic hepatitis C [12]. Most of our patients had liver disease secondary to hepatitis C virus infection, providing an explanation for the observed trend of decreased CRP concentrations.…”
Section: Discussionsupporting
confidence: 52%
“…In chronic hepatitis C, levels of some acute-phase protein, such as C5b-9 levels, CH50, specific C4 activity, and CRP were lower than controls. Interestingly, some of these changes were reversible in patients who responded to HCV treatment [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Also, patients with chronic HCV monoinfection have lower rates of lipid abnormalities than age-and sex-matched healthy subjects [22], and LDL-C concentrations were inversely correlated with the severity of liver disease [23]. Hepatitis C has also been associated with lower C-reactive protein (CRP) levels in both HIVnegative and HIV-positive subjects [24,25]. The beneficial impact of HCV coinfection on lipids and CRP -two independent predictors of cardiovascular disease -has led some to postulate that HCV coinfection may, to some extent, ameliorate the increased cardiovascular risk associated with HIV infection and HAART use [24].…”
mentioning
confidence: 99%